THE INFLUENCE OF SOME PHYSICAL CHARACTERISTICS OF COARSE AND FINE AGGREGATE ON THE STABILITY, FLEXIBILITY AND SKID RESISTANCE OF A HOT ROLLED MIX - Permadi, Edwardus
This thesis describes an investigation of the influence of some physical characteristics of coarse and fine aggregate on the Stability, Flexibility and Skid-Resistance of a Hot Rolled Mix. The hysical caracteristics of coarse aggregate investigated are its content, shape and size, and the physical characteristic of fine aggregate investigated is its shape. Stability is obtained from the Marshall Test, Flexibility is expressed in term of its Tensile Strength using the Indirect Tensile Test, and Skid-Resistance is determined by using the British Pendulum Tester and texture depth measurements. Results show that over the range of coarse aggregate contents investigated, Marshall Stability increases and Marshall Flow decreases with increase in stone content. Marshall Stability at high stone contents is influenced by stone type but the dominant influence on Marshall Quotient over the range of stone contents investigated appears to be fine aggregate type, Tensile Strength of all mixes investigated increases as stone content increases to a maximum values at 40% stone content. Thereafter, tensile strength falls off. At lower stone contents, fine aggregate type is the primary influence on tensile strength, but at higher stone contents, e.g. 55% stone type becomes the significant parameter. British Pendulum Tester is inadequate for describing fully the Skid-Resistance of a surface. Based on Skid Number (SN) values determined from consideration of microtexture and macrotexture, Skid-Resistance increases with increase in stone content. A mix having 40% crushed coarse aggregate content combined with crushed fines aggregate forms the best mix from the view-points of Stability, Flexibility and Skid Resistance.